P-OGC72 Morbidity following oesophagectomy: the long-term re-operation rate after surgical resection in a Scottish tertiary centre. (16th December 2021) - Chien, Siobhan; Gall, Lewis; Khan, Khurram; Macdonald, Andrew; Craig, Carol; MacKay, Colin; Forshaw, Matthew
Abstract: Background: Oesophagectomy remains the best curative option for early stage or locally advanced cancers of the oesophagus and gastro-oesophageal junction. The long-term morbidity associated with oesophagectomy is poorly understood. This study aimed to describe re-operation rates for oesophagectomy-related complications, performed beyond 90 days from index oesophagectomy. Methods: A retrospective cohort study of all oesophagectomies performed in a single tertiary centre between 01 January 2010 and 31 December 2019 was performed. Electronic records were interrogated and patients dichotomised into two groups, with patients that underwent re-operation at ≥ 90 days after oesophagectomy for complications directly related to the index procedure compared to patients who did not have further surgery. All endoscopic interventions were excluded from analysis. The median length of follow-up was 34 months (IQR 20-67). Results: 343 patients were eligible for analysis. Patient demographics and index operative approach were similar between the two groups. Beyond 90 days from surgery, 8.7% of patients (30/343) required a further operation for complications directly related to oesophagectomy. The median time to re-operation was 15.5 months (IQR 12-29). 28 out of a total of 38 re-operations performed (73.7%) were for wound complications (including 15 incisional hernia repairs and 7 excision of stitch sinus). Development of a wound infection in the immediate post-operative period was associated with an increased rate of later re-operation (16.7% vs. 4.8%, p = 0.022). Conclusions: A small but significant number of patients require re-operation following oesophagectomy beyond 90 days of surgery. This should form part of the pre-operative informed consent discussion in order to fully appraise patients and manage expectations. Reducing the incidence of early wound infection appears to be a key factor.